2017
DOI: 10.1186/s12935-017-0395-9
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of suppressor of zest 12 is associated with cervical node metastasis and unfavorable prognosis in tongue squamous cell carcinoma

Abstract: ObjectiveIncreased expression of suppressor of zest 12 (SUZ12), a core component of the polycomb repressive complex 2, contributes to human tumorigenesis and associates with patient prognosis. In the present study, we sought to investigate the expression of SUZ12 and its clinicopathological significance in primary tongue squamous cell carcinoma (TSCC).MethodsThe expression of SUZ12 protein was determined by immunohistochemistry in clinical samples from a retrospective cohort of 72 patients with primary TSCC wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…The enzymes responsible for aberrant epigenetic modifications function as key mediators driving cancer initiation, growth, and metastasis . Our previous studies have indicated that Bmi1, EZH2 and SUZ12, 3 components of polycomb complex responsible for H3K27me3 and H2AK119ub, are overexpressed in oral squamous cell carcinoma and associated with aggressive clinicopathological parameters, and poor prognosis . Herein, as expected, our data from HNSCC cell lines, clinical samples, and transcriptional profiling database of HNSCC revealed that both WDR5 mRNA and protein were elevated in HNSCC as compared to normal counterparts.…”
Section: Discussionsupporting
confidence: 81%
“…The enzymes responsible for aberrant epigenetic modifications function as key mediators driving cancer initiation, growth, and metastasis . Our previous studies have indicated that Bmi1, EZH2 and SUZ12, 3 components of polycomb complex responsible for H3K27me3 and H2AK119ub, are overexpressed in oral squamous cell carcinoma and associated with aggressive clinicopathological parameters, and poor prognosis . Herein, as expected, our data from HNSCC cell lines, clinical samples, and transcriptional profiling database of HNSCC revealed that both WDR5 mRNA and protein were elevated in HNSCC as compared to normal counterparts.…”
Section: Discussionsupporting
confidence: 81%
“…The CD3 and CD8 were selected as markers for total TIL and cytotoxic TIL, respectively. Immunohistochemical staining of CD3 and CD8 was performed on paraffin sections of 4 μm thickness as described previously . Briefly, paraffin sections were deparaffinized in xylene and rehydrated through graded alcohols.…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemical staining of CD3 and CD8 was performed on paraffin sections of 4 lm thickness as described previously. 22 Briefly, paraffin sections were deparaffinized in xylene and rehydrated through graded alcohols. Then, tissue slides were processed in microwave heating in 10 mmol/L citrate buffer (pH 6.0) for 15 minutes for antigen retrieval, and 3% H 2 O 2 for endogenous peroxidase inactivation.…”
Section: Immunohistochemical Staining Of Cd3 and Cd8 In Osccmentioning
confidence: 99%
“…Although, the 5-year survival rate is reported to be up to 50% with early detection, most patients are diagnosed at a late stage, leading to poorer prognosis [ 3 ] and resulting in complications such as the malfunction of mastication, speech, and deglutition, or death. Despite advances in surgical procedures and chemo-radiotherapy, as well as the advent of targeted therapy, clinical outcomes have remained unchanged for decades [ 4 ]. Therefore, it is of primary importance to identify the etiological factors, molecular mechanisms, and pathways of carcinogenesis to discover novel diagnostic and treatment strategies for TSCC.…”
Section: Introductionmentioning
confidence: 99%